Collaborative development in Enterprise Architect 11.1 (Revista Brasileira de Contabilidade e Gestão, 2016)
Collaboration is a consolidated and demonstrably beneficial in the development process of software source codes, but very absent in the development of software models. With the increasing complexity of software and trends pointing to the targeted development of models, what can we do to improve the process of software development models? This research seeks collaboration in an answer to this question and it aims to facilitate the process of initiation of the collaboration in the development of software models presenting methods of collaboration and versioning of models in CASE tool Enterprise Architect version 11.1, corporative edition. This research showed the potential of the collaborative development of models while their immaturity caused by the complexity of the models and the lack of tools, methodologies and work experience reports that help this work methodology.
Keywords: collaborative modeling; Enterprise Architect; case